OPINI AUDIT, AUDITOR SWTICHING, DAN FIRM SIZE TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2020-2023) - Alfa Syaidina Putra; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to examine the influence of audit opinion, auditor switching, and firm size on audit report lag in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research sample was obtained using purposive sampling, resulting in 184 observation data points. The data used are secondary data obtained from the companies' annual reports. Data analysis was conducted using panel data regression with EViews 12 software. The results indicate that, partially, audit opinion has a significant negative effect on audit report lag. Meanwhile, auditor switching and firm size do not have a significant effect on audit report lag.